Impact of early antiretroviral therapy eligibility on HIV acquisition: household-level evidence from rural South Africa - Oldenburg, Catherine; Bor, Jacob; Harling, Guy; Tanser, Frank; Mutevedzi, Tinofa; Shahmanesh, Maryam; Seage, George R.; De Gruttola, Victor; Mimiaga, Matthew J.; Mayer, Kenneth H.; Pillay, Deenan; Bärnighausen, Till (AIDS <London>, 2018)
Objectives: We investigate the effect of immediate antiretroviral therapy (ART) eligibility on HIV incidence among HIV-uninfected household members. - Design: Regression discontinuity study arising from a population-based cohort. - Methods: Household members of patients seeking care at the Hlabisa HIV Treatment and Care Programme in rural KwaZulu-Natal South Africa between January 2007 and August 2011 with CD4+ cell counts up to 350 cells/μl were eligible for inclusion if they had at least two HIV tests and were HIV-uninfected at the time the index patient linked to care (N = 4115). Regression discontinuity was used to assess the intention-to-treat effect of immediate versus delayed ART eligibility on HIV incidence among household members. Exploiting the CD4+ cell count-based threshold rule for ART initiation (CD4+ < 200 cells/μl until August 2011), we used Cox proportional hazards models to compare outcomes for household members of patients who presented for care with CD4+ cell counts just above versus just below the ART initiation threshold. - Results: Characteristics of household members of index patients initiating HIV care were balanced between those with an index patient immediately eligible for ART (N = 2489) versus delayed for ART (N = 1626). There were 337 incident HIV infections among household members, corresponding to an HIV incidence of 2.4 infections per 100 person-years (95% confidence interval 2.5-3.1). Immediate eligibility for treatment reduced HIV incidence in households by 47% in our optimal estimate (hazard ratio = 0.53, 95% confidence interval 0.30-0.96), and by 32-60% in alternate specifications of the model. - Conclusion: Immediate eligibility of ART led to substantial reductions in household-level HIV incidence.